2012
DOI: 10.1021/jm300508n
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3-Nitro-1H-1,2,4-triazole-Based Amides and Sulfonamides as Potential Antitrypanosomal Agents

Abstract: A series of novel 3-nitro-1H-1,2,4-triazole-(and in some cases 2-nitro-1H-imidazole)-based amides and sulfonamides were characterized for their in vitro anti-trypanosomal and antileishmanial activities as well as mammalian toxicity. Out of 36 compounds tested, 29 (mostly 3-nitro-1H-1,2,4-triazoles) displayed significant activity against T. cruzi intracellular amastigotes (IC50 ranging from 28 nM to 3.72 μM) without concomitant toxicity to L6 host cells (selectivity 66 to 2782). Twenty three of these active com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 35 publications
0
68
0
Order By: Relevance
“…The compounds were synthesized in our laboratory as has been described elsewhere (18). Stock solutions of each compound in dimethyl sulfoxide (DMSO; 10 mM) were prepared and checked by liquid chromatography-mass spectrometry/UV analysis (LC-MS/UV) for purity, at 254 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds were synthesized in our laboratory as has been described elsewhere (18). Stock solutions of each compound in dimethyl sulfoxide (DMSO; 10 mM) were prepared and checked by liquid chromatography-mass spectrometry/UV analysis (LC-MS/UV) for purity, at 254 nm.…”
Section: Methodsmentioning
confidence: 99%
“…3-Nitrotriazolebased amides, sulfonamides, amines, and piperazines have dem-onstrated excellent antitrypanosomal activities in vitro and in vivo (18)(19)(20)(21). We have shown that the activities of these compounds against Trypasoma cruzi (the causative parasite of Chagas disease) and Trypanasoma brucei brucei (one of the causative parasites of human African trypanosomiasis) are mediated via 2-electron reduction of the compounds by oxygen-insensitive type I nitroreductase (NTR), which is specific to the trypanosomatids (18,19,21). Since trypanosomatids are not hypoxic and 2-electron-mediated reductions are associated with aerobic conditions, the activation of nitrotriazoles, at least in these parasites, occurs under aerobic conditions.…”
mentioning
confidence: 99%
“…Compounds 3a-m were treated with chloroacetyl chloride at room temperature in acetone to yield derivatives 4a-m [20,21]. Finally, when derivatives 4a-m were allowed to react with different azoles, such as 1H-1,2,4-triazole-3-thiol, imidazole, triazole, tetrazole, and 3-amino-1,2,4-triazole in refluxing dimethylformamide (DMF) in the presence of NaOH [22][23][24][25], the 2-chlorine atom was substituted by these heterocycles, producing the corresponding compounds: 2-((1H-1,2,4-triazol-3-yl)thio)-N- (6-…”
Section: Chemistrymentioning
confidence: 99%
“…We have demonstrated that various chemical classes of 3-nitro-1H-1,2,4-triazolebased compounds exhibit excellent antichagasic activity both in vitro and in vivo (7)(8)(9)(10)(11)(12)(13)(14)(15) and that this activity is in part due to their reductive activation by a type I nitroreductase (NTR) (7,8,(10)(11)(12)(13)(14)(15). Type I NTR is an oxygen-insensitive nitroreductase present in the mitochondrion of trypanosomatids and absent from most other eukaryotes (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Type I NTR is an oxygen-insensitive nitroreductase present in the mitochondrion of trypanosomatids and absent from most other eukaryotes (16)(17)(18)(19). Moreover, 3-nitrotriazole-based compounds seem to be more potent and less toxic than their 2-nitroimidazole-based counterparts (7,8,10,20). Since azoles play a significant role in the inhibition of CYP51 (sterol 14␣-demethylase, an enzyme crucial for the formation of viable membranes and the regulation of metabolic processes) not only in fungi but also in trypanosomatids (21)(22)(23)(24), we have also developed subclasses of 3-nitrotriazole-based compounds that act as bifunctional antichagasic agents: they are substrates for type I NTR, in addition to being reversible inhibitors of T. cruzi CYP51 (12,13).…”
mentioning
confidence: 99%